Exercise-induced shift in right ventricular contraction pattern: novel marker of athlete’s heart? - Lakatos, Bálint Károly; Kiss, Orsolya; Tokodi, Márton; Tősér, Zoltán; Sydó, Nóra; Merkely, Gergő; Babity, Máté; Szilágyi, Mónika; Komócsin, Zsuzsanna; Bognár, Csaba; Kovács, Attila; Merkely, Béla (American journal of physiology. Heart and circulatory physiology, 2018)
Data about the functional adaptation of the right ventricle (RV) to intense exercise are limited. Our aim was to characterize the RV mechanical pattern in top-level athletes using three-dimensional echocardiography. A total of 60 elite water polo athletes (19 ± 4 yr, 17 ± 6 h of training/wk, 50% women and 50% men) and 40 healthy sedentary control subjects were enrolled. We measured the RV end-diastolic volume index (RVEDVi) and ejection fraction (RVEF) using dedicated software. Furthermore, we determined RV global longitudinal (RV GLS) and circumferential strain (RV GCS) and the relative contribution of longitudinal ejection fraction (LEF) and radial ejection fraction (REF) to RVEF using the ReVISION method. Athletes also underwent cardiopulmonary exercise testing [O 2 consumption (V̇o 2 )/kg]. Athletes had significantly higher RVEDVi compared with control subjects (athletes vs. control subjects, 88 ± 11 vs. 65 ± 10 ml/m 2 , P < 0.001); however, they also demonstrated lower RVEF (56 ± 4% vs. 61 ± 5%, P < 0.001). RV GLS was comparable between the two groups (−22 ± 5% vs. −23 ± 5%, P = 0.24), whereas RV GCS was significantly lower in athletes (−21 ± 4% vs. −26 ± 7%, P < 0.001). Athletes had higher LEF and lower REF contribution to RVEF (LEF/RVEF: 0.50 ± 0.07 vs. 0.42 ± 0.07, P < 0.001; REF/RVEF: 0.33 ± 0.08 vs. 0.45 ± 0.08, P < 0.001). Moreover, the pattern of RV functional shift correlated with V̇o 2 /kg (LEF/RVEF: r = 0.30, P < 0.05; REF/RVEF: r = −0.27, P < 0.05). RV mechanical adaptation to long-term intense exercise implies a functional shift; the relative contribution of longitudinal motion to global function was increased, whereas the radial shortening was significantly decreased, in athletes. Moreover, this functional pattern correlates with aerobic exercise performance, representing a potential new resting marker of an athlete’s heart. NEW & NOTEWORTHY Intensive regular physical exercise results in significant changes of right ventricular morphology and function. By separate quantification of the right ventricular longitudinal and radial function, a relative dominance of longitudinal motion and a decrease in radial motion can be observed compared with sedentary controls. Moreover, this contraction pattern correlates with cardiopulmonary fitness. According to these results, this functional shift of the right ventricle may represent a novel marker of an athlete’s heart.